Implementation of Problem Based Learning to Develop Student's Character in Social Arithmetic Lesson - Muhammad Farid Nasrulloh; Khoirun Nisa' (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to determine the effectiveness of the application of problem-based learning in developing students' character in social arithmetic material. The approach used in this research is a quantitative approach with a quasi-experimental type of research. This study used all students of class VII D SMP Negeri 1 Kudu which were divided into two groups, namely the control group and the experimental group. The instruments used in this study were tests, questionnaires. The test is used to determine the student's ability while the questionnaire is to determine the student's character in problem-based learning. The prerequisite test used in this study used the normality test and homogeneity test, with a = 0.05. Hypothesis testing in this study using independent sample t-Test on IBM SPSS.21 for windows. The results showed that the problem based learning model had a positive and significant effect on the development of students' character.